2021
DOI: 10.3389/fneur.2021.660087
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Neuropathologic Mechanisms of SARS-CoV-2 Infection

Abstract: The current pandemic caused by the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a public health emergency. To date, March 1, 2021, coronavirus disease 2019 (COVID-19) has caused about 114 million accumulated cases and 2.53 million deaths worldwide. Previous pieces of evidence suggest that SARS-CoV-2 may affect the central nervous system (CNS) and cause neurological symptoms in COVID-19 patients. It is also known that angiotensin-converting enzyme-2 (ACE2), the primary receptor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 217 publications
(171 reference statements)
0
79
0
1
Order By: Relevance
“…The clinical manifestations of autoimmune neurological disorders such as multiple sclerosis (MS) or Guillain–Barré syndrome (GBS) have been reported in COVID-19 case studies. 3 For example, following 2–3 weeks of SARS-CoV-2 infection a 29-year-old female developed multiple sclerosis with right optic neuritis; 4 MS-like demyelination may occur in COVID-19 patients due to autoimmune mechanisms resulting from T-lymphocyte activation secondary to M1 microglia phenotype activation with associated inflammatory mediator release. As presented in another case report, myelin oligodendrocyte glycoprotein antibody-positive neuromyelitis optica was observed in a 26-year-old male who presented with bilateral optic neuritis and extensive longitudinal transverse myelitis, occurring several days after COVID-19 symptom onset.…”
Section: Autoimmune Neurodegenerative Disorders and Covid-19mentioning
confidence: 99%
“…The clinical manifestations of autoimmune neurological disorders such as multiple sclerosis (MS) or Guillain–Barré syndrome (GBS) have been reported in COVID-19 case studies. 3 For example, following 2–3 weeks of SARS-CoV-2 infection a 29-year-old female developed multiple sclerosis with right optic neuritis; 4 MS-like demyelination may occur in COVID-19 patients due to autoimmune mechanisms resulting from T-lymphocyte activation secondary to M1 microglia phenotype activation with associated inflammatory mediator release. As presented in another case report, myelin oligodendrocyte glycoprotein antibody-positive neuromyelitis optica was observed in a 26-year-old male who presented with bilateral optic neuritis and extensive longitudinal transverse myelitis, occurring several days after COVID-19 symptom onset.…”
Section: Autoimmune Neurodegenerative Disorders and Covid-19mentioning
confidence: 99%
“…IL-6-dependent Th17 activation and differentiation is essential for neutrophil granulocyte migration ( 42 ). Experimental work showed that SARS-CoV-2-infected glial cells secrete increased levels of IL-6 and TNFα ( 5 , 43 ). IL-6 can alter neuronal and glial activity and induce cell death, olfactory loss or induction of hyperphosphorylation of the tau protein in axons, triggering their degeneration.…”
Section: Potential Role Of Viruses In the Context Of Autoimmune Encephalitismentioning
confidence: 99%
“…Microvascular damage in the systemic inflammatory response to SARS-CoV-2 is thought to promote the occurrence of encephalopathy in severe COVID-19 disease ( 5 ). Inflammatory mediators produced by the alveolar epithelium, macrophages and leukocytes may contribute to endothelial inflammation, increased vascular permeability, edema, and increased synthesis and consumption of coagulation factors.…”
Section: Potential Role Of Viruses In the Context Of Autoimmune Encephalitismentioning
confidence: 99%
See 1 more Smart Citation
“…It could also be due to direct viral invasion of the nervous system. There are reports of SARS-CoV-2 detection in the CSF and in postmortem brain tissue, the latter even in the absence of respiratory illness [ 10 ]. Evidence of direct and widespread neural infection is still being investigated intensely.…”
Section: Introductionmentioning
confidence: 99%